Equity mispricing and the adjustment toward target leverage: Evidence from the UK - Dang, Thi Uyen Thao (2017)
The objective of this paper is to provide an empirical analysis of the influence of equity misevaluation on the speed of adjustment toward target leverage in the UK market over the period of 1993-2016. The study introduces a set of better measures of equity mispricing and implements the standard partial adjustment model to estimate the speed at which firms revert to their target leverage. The average firm is expected to reduce the distance from its target level by 31-33% each year or it takes approximately three years for the firm to adjust back to its optimal capital structure after attempts to time the market in favorable conditions, equivalently. Especially, the study documents strong evidence for pronounced heterogeneity in the target leverage adjustment speed across the sample. For example, the firm which is above its target level (i.e. calls for equity issuance or debt repurchase) tends to revert more rapidly in the period of overvaluation relative to undervaluation. Correspondingly, looking at firms below target levels (i.e. needs to issue debt or repurchase equity), they adjust faster to target levels in the presence of undervaluation. The results are robust to different proxies for leverage in the partial adjustment model and alternate methods of measuring mispricing. While the study is highly consistent with Warr et al. (2012), it challenges the evidence of Baker and Wurgler (2002) about the permanent effect of market timing on capital structure.